Wideband and High-Efficiency SIW Cavity-Backed Magneto-Electric Dipole Antenna Array - Guang Sun; Yi Liu; Taolin Liu; Hu Yang (International Journal of Antennas and Propagation)
In this paper, a compact, wideband, and high-efficiency substrate integrated waveguide (SIW) feeding cavity-backed aperture-coupled magneto-electric (ME) dipole antenna element and its array are proposed. Firstly, an SIW cavity-backed and a modified bowtie dipole are designed for the antenna element which makes it possess a high gain and wide impedance bandwidth. The antenna element covers an impedance bandwidth of 66.3% from 10.7 to 21.3 GHz with a peak gain of 10.3 dBi. Secondly, a 4 × 4 array is designed using the proposed antenna element. And a full-corporate substrate integrated waveguide feeding network is introduced to excite the array elements for the antenna application with wide bandwidth and high efficiency. For validation, a prototype of 4 × 4 array is fabricated by standard printed circuit board (PCB) facilities and further measured. The measured −10 dB impedance bandwidth of the proposed 4 × 4 antenna array is 30% (12.75–17.25 GHz) with its gain being 18.2–20.9 dBi within the entire band. The measured maximum aperture efficiency of the antenna array is 94% at 14.92 GHz. Notably, the measured results agree well with simulations, and it shows great advantages over other similar antennas on efficiency and bandwidth.